Kin-Dza-Dza - Kančeli, Gija Aleksandrovič 1935-2019 (Bildstörung, 2021)
"Kin-dza-dza" is one of the strangest artefacts in all of Soviet cinema. It's a science fiction satire in which Vladmir and Gedevan, a gruff Russian construction worker and a Georgian student, find themselves accidentally transported to Pluke, a barren desert-world with a barbaric, bureaucratic society. Gradually realising that they are not in a "capitalist country", the two men begin a long and farcical voyage home that more closely resembles the theatre of the absurd than it does any preconceived notion of cinematic science fiction. [...]" [electricsheepmagazine.co.uk]
Orig.: Sowjetunion 1986
Bonus: ein Mann vom Planeten Plük, Russland 2010 (45 Min.), Georgi Danelija - zwischen Fiktion und Realität, Russland 2012 (39 Min.), Interview mit Regisseur Georgi Danelija, Trailer, Booklet
Keywords: Film; DVD-Video